Polarization dependent high refractive index metamaterial with metallic dielectric grating structure in infrared band - Li, Jianmin; Chen, Peng; Fang, Bo; Cai, Jinhui; Zhang, Le; Wu, Yinglai; Jing, Xufeng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
According to the theory of high refractive index of metamaterials, a composite structure of metal dielectric grating was designed to achieve high refractive index in infrared band. Based on the S-parameter inversion algorithm, we extracted the effective permittivity, the effective permeability, and the effective refractive index of the designed metamaterial. By changing the geometric parameters of the composite grating metamaterial structure, the effective refractive index of the designed metamaterial reaches more than 8.0 at the infrared resonance frequency. This is a high refractive index that many natural materials cannot achieve. It is noteworthy that the metamaterial structure has obvious polarization sensitivity. The metamaterial structure has both high refractive index and wide-band zero refractive index properties when different polarized light is incident. At the same time, we further investigate the influence of metamaterial geometric parameters on the effective refractive index of metamaterials. Also, we propose a double grating metamaterial structure to obtain more degrees of freedom of metamaterial on the effective refractive index.
Optica Applicata, Vol. 52, 2022, nr 3, s. 441-460
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; metamaterials; high refractive index; infrared band